1992
DOI: 10.1172/jci115930
|View full text |Cite
|
Sign up to set email alerts
|

Human bactericidal/permeability-increasing protein and a recombinant NH2-terminal fragment cause killing of serum-resistant gram-negative bacteria in whole blood and inhibit tumor necrosis factor release induced by the bacteria.

Abstract: The bactericidal/ permeability-increasing protein (BPI) ofneutrophils and BPI fragments neutralize the effects of isolated Gram-negative bacterial lipopolysaccharides both in vitro and in vivo. Since endotoxin most commonly enters the host as constituents of invading Gram-negative bacteria, we raised the question: Can BPI and its bioactive fragments also protect against whole bacteria? To determine whether the bactericidal and endotoxin-neutralizing activities of BPI / fragments are expressed when Gram-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(144 citation statements)
references
References 50 publications
6
137
1
Order By: Relevance
“…rBPI 23 [2], a human recombinant NlIj-terminal fragment of BPI possessing LPS-neutralizing activity [14], was obtained from XOMA (Berkeley, CA). Thaumatin (XOMA), used as a control protein, has a molecular weight and isoelectric point similar to rBPI 23 [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…rBPI 23 [2], a human recombinant NlIj-terminal fragment of BPI possessing LPS-neutralizing activity [14], was obtained from XOMA (Berkeley, CA). Thaumatin (XOMA), used as a control protein, has a molecular weight and isoelectric point similar to rBPI 23 [2].…”
Section: Methodsmentioning
confidence: 99%
“…By both flow cytometry and confocal microscopy, we observed that rBPI 2 3 • a recombinant Nl-ly-rerminal fragment of BPI [2,14], reduced LPS binding to monocytes when added to normal plasma containing LBP. Low residual LPS binding was observed.…”
Section: Time-dependent Inhibition By Rbpi 23 Of the Lbp-mediated Binmentioning
confidence: 99%
“…Because low concentrations of BPI can inhibit LBP-promoted LPS signaling (23)(24)(25), we investigated whether low (substoichiometric) concentrations of BPI can block the enhancing effects of LBP on the fluorescence of FITC-LPS. To this end, the fluorescence of FITC-LPS was monitored both after preincubation for 30 min with increasing amounts of BPI to permit formation of LPS-BPI complexes and after subsequent addition of LBP.…”
Section: Comparison Of Effects Of Lbp and Bpi On Fitc-lps-mentioning
confidence: 99%
“…(5). BPI has the effect of neutralizing endotoxin and directly killing GNB, but has no adverse effect on eukaryotic cells (6,7). The phase II/III trial of rBPI 23 and rBPI 21 demonstrated that administration of rBPI has effect on GNB infected patient (8,9).…”
Section: Introductionmentioning
confidence: 99%